Teacher Certification Policy On State Elementary Schools - Fahrurroji Sidik; Widayati Widayati (Universitas Islam Sultan Agung, 2020)
The purpose of this study was to determine how the teacher certification policy implementation process and how the certification affects the professionalism of teachers at Wanoja 01 Elementary School and to find out what are the constraints or inhibiting factors in the certification policy. This study uses a sociological juridical approach that uses descriptive research with a qualitative approach with the technique of determining informants using purposive techniques and is developed through the snowball technique. The results of this study indicate that the implementation of the teacher certification policy at Wanoja 01 Elementary School, Salem Sub-District is good and fulfills the six variables of the implementation of public policy models of Van Meter and Van Horn. Certification has a positive role in the level of professionalism of teachers at Wanoja 01 Elementary School, Salem Sub-District. From the results of its implementation, there are several obstacles or obstacles faced. Such as the delay in disbursing the teacher professional allowance and the effect of teacher certification that has not shown significant results for teacher effectiveness in improving quality and quality.